(untitled) (MAUSAM, 1975)
Regular measurements of the dust and nuclei contient of the air near the ground at Poona were made during 1967-69 to study the characteristic elements of natural pollution n6ar the ground, its origin and its variation with time seasons and altitude. The electrical field strength the positive and negative conductivity of the air and the number of positively and negatively charged small ions in the atmosphere near the ground were also measured at the same time. These observations were repeated at two mountain stations during February and June 1969. The dust content and the electric field show seasonal and diurnal variations opposite to those of the small ion density and electrical conductivity. Thus, while the electric field is a maximum in winter, the conductivity and small ion content is a maximum during the monsoon months and the dust content a maximum in the pre-monsoon summer months. A marked increase in the electric field and the dust and condensation nuclei content is observed since similar measurements were last made in 1933-1937 at Poona, with a corresponding decrease in small ion count and conductivity. These large variations are associated with the increased industrialisation and urbanisation of the regions around Poona during the last thirty years.